Physical Mobility Impairment and Risk for Cardiovascular Disease - Mary L. Wilby (Mary Ann Liebert, 2019)
Background: People with disabilities (PWD) often self-report reduced access to preventive health services and poorer health than people without disability. Risk factors for chronic disease are more prevalent in PWD, increasing risk for secondary conditions including cardiovascular disease (CVD). Methods: Logistic regression was used to analyze data from the 2016 Behavioral Risk Factor Surveillance Survey to explore the relationship between disability with mobility impairment and CVD. Results: Difficulty walking and climbing stairs significantly predicted concomitant CVD and diabetes in logistic regression models. Conclusion: Information from this study may be useful in addressing CVD risk for adults with mobility impairments.